2016
DOI: 10.5539/ijb.v8n4p21
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Occurrence of Different Grasshoppers Species (Orthoptera: Acridoidea) in Uruguay

Abstract: This paper aims at knowing the seasonal occurrence of grasshoppers (Orthoptera: Acridoidea) in Uruguay. The populations of these native herbivores are generally in equilibrium, although population increases were recorded under certain conditions, causing significant economic loss. The population was monitored during five seasons on sites located in the departments of Florida and Durazno. The insects were categorized into young nymphs (I, II and III), older nymphs (IV and V), and adults. At each sampling time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…In the present study we observed a species richness equal to that was obtained by Lorier et al (2016) and Zerbino et al (2016) in acridomorph surveys in other grassland areas of Uruguay. We found more species than were recorded by Weiss et al (2012) in pastures in Germany (S = 13), by Pocco et al (2010, 2013 in grasslands of Argentina, but less than recorded by Kemp (1992) for rangelands in the United States and by Andersen et al (2001) in Australia (S = 40).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the present study we observed a species richness equal to that was obtained by Lorier et al (2016) and Zerbino et al (2016) in acridomorph surveys in other grassland areas of Uruguay. We found more species than were recorded by Weiss et al (2012) in pastures in Germany (S = 13), by Pocco et al (2010, 2013 in grasslands of Argentina, but less than recorded by Kemp (1992) for rangelands in the United States and by Andersen et al (2001) in Australia (S = 40).…”
Section: Discussionsupporting
confidence: 81%
“…We found more species than were recorded by Weiss et al (2012) in pastures in Germany (S = 13), by Pocco et al (2010, 2013 in grasslands of Argentina, but less than recorded by Kemp (1992) for rangelands in the United States and by Andersen et al (2001) in Australia (S = 40). Gomphocerinae and Melanoplinae were the most abundant subfamilies of Acrididae, coinciding with other communities of Acridomorpha in grasslands of the south of South America (Cigliano and Lange 1998;Torrusio et al 2002;Pocco et al 2010;Lorier et al 2016;Zerbino et al 2016).We found common grassland species like Dicroplus elongatus, Dicroplus pratensis, Scotussa lemniscata, Laplatacris dispar, Amplytropidia austra lis, and Orphulella punctata , and others associated with wetlands and aquatic and semiaquatic areas, like Lep tysma argentina, Haroldgrantia lignosa, Metaleptea adspersa, Chromacris speciosa, and Zoniopoda iheringi (Carbonell et al 1967;COPR 1982;Bentos-Pereira and Lorier 1991).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations